2018
DOI: 10.1634/theoncologist.2017-0598
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Elderly Patients with Advanced Soft Tissue Sarcoma Treated with First-Line Chemotherapy: A Pooled Analysis of 12 EORTC Soft Tissue and Bone Sarcoma Group Trials

Abstract: This analysis demonstrates that elderly patients with advanced soft tissue sarcoma are underrepresented in clinical trials of first-line chemotherapy by the European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group. Furthermore, the elderly participants were generally of excellent performance status, which is not representative of an unselected elderly population. These data provide rationale for development of novel trials for elderly patients that are not only for "elite" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Notably, the median age of patients included in this study was 79 years, much older than the threshold of 65 years commonly used to define elderly patients. 23 This population is usually greatly underrepresented in STS trials, as reported recently by the European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group. 23 In this analysis of 13 trials, the percentage of enrolled patients aged ≥65 years was only 12.4%, and the median age within this small percentage of patients was relatively low (68 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the median age of patients included in this study was 79 years, much older than the threshold of 65 years commonly used to define elderly patients. 23 This population is usually greatly underrepresented in STS trials, as reported recently by the European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group. 23 In this analysis of 13 trials, the percentage of enrolled patients aged ≥65 years was only 12.4%, and the median age within this small percentage of patients was relatively low (68 years).…”
Section: Discussionmentioning
confidence: 99%
“…23 This population is usually greatly underrepresented in STS trials, as reported recently by the European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group. 23 In this analysis of 13 trials, the percentage of enrolled patients aged ≥65 years was only 12.4%, and the median age within this small percentage of patients was relatively low (68 years). This is in contrast to the fact that 40% to 50% of new diagnoses of STS each year are performed in elderly patients and further highlights the burning issue of the age gap between clinical trials and everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In contrast, key issues that must be considered in treatment of elderly patients are physiological changes associated with aging, functional and role functioning, comorbidities, cognitive status and polypharmacy. 19 Lack of representation in clinical trials is seen in both AYA and elderly patients. 20 , 21 A recent study identified significant age-related differences in the sarcoma patient journey that are not only related to variations in sarcoma subtypes, such as more incorrect diagnoses and higher burden of treatment in younger patients and less referral to rehabilitation services in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Another important point of view is that elderly patients are generally underrepresented or excluded from cancer clinical trials, whereas they represent an increasing population in "real life" medical oncology [9,10]. This has negatively impacted our knowledge of sarcoma treatment efficacy for this age group, although the scenario seems to be evolving in the last few years.…”
Section: Introductionmentioning
confidence: 99%